Karakteristik Kimia Permen Jelly Buah Naga dan Daun Kelor - Wanda Lestari; Faras Anzely Sukma; Rika Fitri Ilvira; Sudana Fatahillah Pasaribu; Abdul Hairuddin Angkat (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Jelly candy is a transparent and clear physical appearance, produced from a combination of fruit juices, gelling agents, or flavoring ingredients. Objectives; To determine the acceptability and chemical quality (calcium, potassium, vitamin C, and water content) of jelly candy made from dragon fruit and moringa leaves. Method; The research used a Completely Randomized Design (CRD) experiment with 5 treatments and 2 repetitions, resulting in 10 experimental designs. Acceptability testing was carried out by 30 moderately trained panelists. Data analysis used Kruskal Wallis and continued with the Bonferroni test. Results; results showed that the optimal formulation was 90 grams of dragon fruit and 10 grams of moringa flour, which was rated positively. The hedonic quality test revealed a purple color, a chewy texture, a flavor predominantly of dragon fruit with a slight taste of moringa leaves. The formulation contained 601 mg of calcium, 112 mg of potassium, 26.77% water, and 10.20 mg of vitamin C per 100 grams. Conclusion; The candy formulation with 90 grams of dragon fruit and 10 grams of moringa flour received a favorable rating, demonstrating a purple color, chewy texture, predominant dragon fruit flavor with a hint of moringa, and appropriate nutritional content.